1983
DOI: 10.1111/j.1365-2125.1983.tb02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam: sleep and performance studies in middle age.

Abstract: 1 Effects of 10, 20 and 30 mg midazolam on sleep and on performance the next day were studied in six healthy adult males aged between 47 and 53 years. The study was double-blind, placebo-controlled and included another rapidly eliminated benzodiazepine (brotizolam, 0.25 mg) as an active control. 2 With 10 mg midazolam, sleep-onset latency was quicker, and the duration and percentage of stage 2 sleep was increased over the first 6 h. Effects of 20 and 30 mg midazolam were similar to each other. Sleep onsets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The present and previous studies (6,7) suggest that the most appropriate role of midazolam is for sleeponset insomnia or for short periods of sleep, and this would support the analysis of Amrein et al (8). Indeed, the very rapid absorption of midazolam (9) indicates that relatively low doses of the drug would be appropriate, and the most useful dose may be ~7.5 mg. On the other hand, the somewhat slower elimination of brotizolam (0.125-0.25 mg) would appear to have the potential to sustain sleep (0) yet still be free of residual effects (11,12) and of accumulation on daily ingestion (3).…”
Section: Discussionsupporting
confidence: 64%
“…The present and previous studies (6,7) suggest that the most appropriate role of midazolam is for sleeponset insomnia or for short periods of sleep, and this would support the analysis of Amrein et al (8). Indeed, the very rapid absorption of midazolam (9) indicates that relatively low doses of the drug would be appropriate, and the most useful dose may be ~7.5 mg. On the other hand, the somewhat slower elimination of brotizolam (0.125-0.25 mg) would appear to have the potential to sustain sleep (0) yet still be free of residual effects (11,12) and of accumulation on daily ingestion (3).…”
Section: Discussionsupporting
confidence: 64%
“…COSTA E SILVA ETAL. (Gudgeon & Hindmarch, 1983;Hauri et al, 1983;Nicholson & Stone, 1983;Vogel & Vogel, 1983;Ziegler et al, 1983), have shown that, following 15 mg midazolam, performance scores will run in parallel to the sedative effect, showing impairment (at its maximum 1-2 h after ingestion) followed by a gradual return to baseline values 4-5 h after drug intake. The findings after administration of 0.5 mg triazolam are less consistent.…”
Section: Effects On Sleepmentioning
confidence: 99%
“…The results obtained in open trials and confirmed in double-blind studies have shown midazolam to be very effective in the treatment of sleep disorders of different degree Scollo-Lavizzari, 1983; Vogel & Vogel, 1983). In comparative studies with other benzodiazepine derivatives, midazolam has frequently been shown to be superior to the reference compounds, particularly with regard to dimininishing the sleep onset latency (Helcl et al, 1981;Feldmeier & Kapp, 1983;Nicholson & Stone, 1983). Vesparax (150 mg secobarbital, 50 mg brallobarbital, 50 mg hydroxyzine) is a fast-acting hypnotic agent with a reliable therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…In comparative studies with other benzodiazepine derivatives, midazolam has frequently been shown to be superior to the reference compounds, particularly with regard to dimininishing the sleep onset latency (Helcl et al, 1981;Feldmeier & Kapp, 1983;Nicholson & Stone, 1983).…”
Section: Introductionmentioning
confidence: 99%